Driver or inhibitor for innovation?: Modeling and simulating contradictory forces and dynamic aspects of team diversity. Issue 2 (18th December 2017) - Kreidler, Anja; Tilebein, Meike
Abstract : Purpose: Literature is unanimous about the effects of functional diversity in new product development teams. This paper uses simulation modeling to investigate the contradictory and dynamic effects of functional team diversity on innovation revealed by empirical literature. This paper aims to start a discussion on this dynamic perspective of team diversity. Design/methodology/approach: This paper presents a systemic approach toward investigating the contradictory and dynamic effects of functional team diversity on innovation by creating a simplified System Dynamics model of functional diversity in new product development teams. Findings: Although the simulation model is highly simplified, it can integrate the contradictory results of empirical data and the dynamic component of teamwork. Therefore, it offers a new approach to investigating the effects of functional diversity on team innovation. Research limitations/implications: The model is highly simplified and exemplary. No actual data are included, thus limiting the results as fully theoretical. Originality/value: Empirical studies often analyze the effects of functional diversity on innovation in new product development teams. However, empirical data are unclear regarding the nature of the effects of functional diversity on innovation. Therefore, functional diversity is chosen for the simulation model as being the most controversially discussed diversity attribute. By applying a simulation model to the problem and adding a dynamic component to teamwork, we are contributing to the explanation for the contradictory findings in literature.